2008
DOI: 10.1016/j.biopsych.2007.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Rostral Anterior Cingulate Cortex Volume Correlates with Depressed Mood in Normal Healthy Children

Abstract: BACKGROUND-The rostral anterior cingulate cortex (rACC) has been implicated as a structural neural correlate of familial major depressive disorder, raising the possibility that the structure of this region may act as a biologic marker of depression vulnerability. The aim of the current study was to determine whether children and adolescents with depressive symptoms have lower rACC volume relative to those without symptoms and examine how a positive family history of depression affects this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
71
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 58 publications
14
71
0
Order By: Relevance
“…Similarly, McDonald et al (2004) showed that reduced volume of the right 'perigenual' ACC region (including both the sgACC and the 'pregenual' ACC (pgACC) anterior to the corpus callosum); was associated with increasing genetic risk for BD (based upon numbers of affected relatives). It has also been reported that the left perigenulate ACC volume was smaller in boys with subclinical depressive symptoms, and that the negative correlation between left sgACC volume and depression symptoms was particularly robust in boys with a family history of depression (Boes et al, 2008). Notably, the short allele of the serotonin transporter promoter region length polymorphism (5HTT-PRL) has been identified as a genetic factor that is associated with both an increased vulnerability for developing MDD within the context of stress (Caspi et al, 2003) and a reduction in sgACC gray matter volume (Pezawas et al, 2005).…”
Section: Brain Structural Abnormalities In Mood Disordersmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, McDonald et al (2004) showed that reduced volume of the right 'perigenual' ACC region (including both the sgACC and the 'pregenual' ACC (pgACC) anterior to the corpus callosum); was associated with increasing genetic risk for BD (based upon numbers of affected relatives). It has also been reported that the left perigenulate ACC volume was smaller in boys with subclinical depressive symptoms, and that the negative correlation between left sgACC volume and depression symptoms was particularly robust in boys with a family history of depression (Boes et al, 2008). Notably, the short allele of the serotonin transporter promoter region length polymorphism (5HTT-PRL) has been identified as a genetic factor that is associated with both an increased vulnerability for developing MDD within the context of stress (Caspi et al, 2003) and a reduction in sgACC gray matter volume (Pezawas et al, 2005).…”
Section: Brain Structural Abnormalities In Mood Disordersmentioning
confidence: 83%
“…These studies have implicated subgenual PFC regions of the infralimbic cortex (BA 25) (eg, Coryell et al, 2005) and the adjacent sgACC corresponding to BA 24sg (eg, Ö ngür et al, 1998a, b, 2003Drevets et al, 1997a) (Figure 9). The extant data suggest this volumetric reduction exists early in illness and in young adults at high familial risk for MDD (Botteron et al, 2002;Hirayasu et al, 1999;Drevets et al, 2004b;Boes et al, 2008). Nevertheless, a longitudinal study also has shown progression of the abnormality in subjects with psychotic mood disorders (Koo et al, 2008).…”
Section: Brain Structural Abnormalities In Mood Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the frequency of subthreshold depression in adolescents, with a lifetime prevalence reported as high as 26%, 4 only one neuroimaging report 8 restricted to the rostral anterior cingulate cortex (rACC) showed that boys with subthreshold depressive symptoms, but not girls, had smaller rACC volume than those with no depressive symptoms. The differences are more widespread in adolescents with MDD, since reduced gray matter volumes have been reported in frontal, limbic, and striatal regions such as prefrontal cortex (PFC), 9,10 ACC, 11 amygdala, 12 hippocampus, 13 and caudates.…”
Section: Introductionmentioning
confidence: 99%
“…37,57 Smaller volumes of the rostral cingulate cortex have been found in boys with subclinical depression. 3 Metabolic studies have confirmed that the rostral cingulate cortex shows increased glucose utilization in patients who respond to antidepressants (as opposed to nonresponders), with metabolic activity predicting the magnitude of the response to pharmacotherapy. 37,53,57 Rostral cingulate cortex involvement in depression has also been corroborated by functional MR imaging data.…”
Section: Inferior Thalamic Pedunclementioning
confidence: 98%